Street gangs a secret history - DeHart, Greg.; Mudd, Roger, 1928-2021.; History Channel (Television network); Arts and Entertainment Network; New Video Group; Termite Art Productions ([New York] : A&E Television Networks : Distributed in the U.S. by New Video, 2000)
Examines the history, psychology and role of gangs in America throughout the years, from their first appearances in urban immigrant communities to the sophisticated operations that are expanding the influence of gangs like the Crips and Bloods deep into the heartland today.
Originally broadcast as a segment of the television series "Time machine" on the History Channel.
Editor, Randall M. Boyd ; director of photography, Richard Pendleton and Stephen Schultz ; narrator, D. Paul Thomas ; music, Mark Leggett.
Host: Roger Mudd.
DVD ; all area code.
Keywords: Gangs -- United States -- History; Gangs